Applied Research on Community Empowerment of Teaching Derivational and Inflectional Morphemes to Pondok An Nahdloh, Selangor, Malaysia - Zaniar, Savira; Djuwari, Djuwari; Didien Afandi, Mujad; Rihlah, Jauharotur; Susanto, Fajar Annas (Jurnal Indonesia Sosial Sains, 2025)
This community service initiative took place at Pondok An Nahdloh, an Islamic boarding institution in Selangor, Malaysia, particularly serving the educational requirements of children of Indonesian migrant workers. Despite the integration of religious and general language training, students encounter difficulties in acquiring derivational and inflectional morphemes due to linguistic interference, inconsistent pedagogical approaches, and restricted access to resources. To address these issues, the project applied a multilingual and contextualized teaching approach that incorporated contrastive analysis, translanguaging strategies, and the use of familiar cultural and religious contexts. Materials suitable for various age groups were created, comprising interactive games, organized exercises, and digital resources like flashcards, quizzes, and augmented reality experiences. Furthermore, capacity-building workshops were conducted for educators and community people to guarantee sustainability. The project results indicated higher student skill in morpheme application, heightened motivation for language acquisition, and improved teacher effectiveness in providing consistent instruction. This approach cultivated a sustainable language learning environment, enhanced community engagement, and advanced the overall empowerment of the pesantren.